2022
DOI: 10.1111/1754-9485.13416
|View full text |Cite
|
Sign up to set email alerts
|

Improving the synergistic combination of programmed death‐1/programmed death ligand‐1 blockade and radiotherapy by targeting the hypoxic tumour microenvironment

Abstract: Immune checkpoint inhibition with PD-1/PD-L1 blockade is a promising area in the field of anti-cancer therapy. Although clinical data have revealed success of PD-1/PD-L1 blockade as monotherapy or in combination with CTLA-4 or chemotherapy, the combination with radiotherapy could further boost antitumour immunity and enhance clinical outcomes due to the immunostimulatory effects of radiation. However, the synergistic combination of PD-1/PD-L1 blockade and radiotherapy can be challenged by the complex nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 166 publications
(340 reference statements)
0
1
0
Order By: Relevance
“…Hypoxia is a hallmark of solid tumors that reduces their susceptibility to radiation therapy and is a driver of immunotherapy resistance (145). Given the enormous benefits of targeting hypoxia for RT and immunotherapy, a number of regiments have been developed to ameliorate hypoxia to increase the efficacy of radiotherapy combined with immunotherapy, including increasing oxygen supply to tumors, inhibiting mitochondrial oxidative phosphorylation (OXPHOS), inhibiting HIF activity (146).…”
Section: Ameliorate Hypoxia To Induce Oxidative Stress To Enhance Rad...mentioning
confidence: 99%
“…Hypoxia is a hallmark of solid tumors that reduces their susceptibility to radiation therapy and is a driver of immunotherapy resistance (145). Given the enormous benefits of targeting hypoxia for RT and immunotherapy, a number of regiments have been developed to ameliorate hypoxia to increase the efficacy of radiotherapy combined with immunotherapy, including increasing oxygen supply to tumors, inhibiting mitochondrial oxidative phosphorylation (OXPHOS), inhibiting HIF activity (146).…”
Section: Ameliorate Hypoxia To Induce Oxidative Stress To Enhance Rad...mentioning
confidence: 99%
“…The mechanism of this improvement was further studied, and it was found that CD8+ T lymphocytes were increased in the tumor site, M1/M2 macrophage ratios were increased, and immunosuppressive myeloid cells were decreased in the combination treatment in both primary and secondary metastatic tumor sites. They also found that tumor hypoxia was somewhat relieved by utilizing these NPs, which has been identified as a limiting factor for radio-immunotherapy/abscopal responses (Mudassar et al, 2022). Of note, MnO 2 NPs have previously been used to catalyze the breakdown of hydrogen peroxide into molecular oxygen, which increases the efficacy of RT by increasing the production of tumoricidal ROS and relieving tumor hypoxia (Prasad et al, 2014).…”
Section: Considerations For the Preclinical Study Of Combining Icis W...mentioning
confidence: 99%
“…Due to the hypoxic tumour microenvironment and amplified PD-L1 expression, the response to RT is impaired. Recent promising experimental studies have focused on targeting the hypoxic tumour environment as well as improved anti-PD-L1 efficacy with specifically developed nanoparticles to improve the efficacy of (immune-RT [77,78]. Other techniques to improve the efficacy of preoperative RT are being investigated in phase I/II trials, such as dose intensification only to the posterior wall for high-risk margins of RPS through "dose painting" with proton or photon IMRT (NCT01659203) [79].…”
Section: Perioperative Radiotherapymentioning
confidence: 99%